Living with Difference: Experiences of Adolescent Girls with Cleft Lip and Palate. (March 2013) - Tiemens, Kim; Nicholas, David; Forrest, Christopher R.
Objective: This study explored the experiences of adolescent girls with cleft lip and palate who were preparing for orthognathic surgery. Design: A qualitative study, based on a phenomenological approach, explored adolescents' experiences. Two 1-hour semistructured interviews were conducted before surgery, and member checking was employed to verify findings with each participant. Setting: A tertiary care pediatric hospital in central Canada. Participants: A criterion sampling technique was used to recruit a sample of seven participants with cleft lip and palate ranging in age from 15 to 20 years who were scheduled for cleft orthognathic surgery. Results: Participants described experiencing teasing, bullying, and stares. In many cases, participants sought to resist and dismiss negative social attitudes about their visible difference while working to combat this with a positive view of who they really are. To varying degrees, participants felt constricted in engaging in the community as they were worried what others thought of their visible difference. They worked at finding ways to reduce the impact of social stigma through coping strategies, social supports, and reconstructive surgery. Conclusions: Adolescent girls can experience strain associated with living with a facial difference; however, they find strategies to cope with the perception of difference. Reconstructive surgery is viewed as a means to increase confidence. Further intervention is needed in understanding and addressing stigma and fostering resiliency related to female adolescents living with a facial difference.